Chinese cruise customers loyalty: the impact of customer participation and service personal values. Issue 1 (17th April 2020) - Wu, Hui; Lv, Xiaoxiao; Cavusoglu, Muhittin; Cobanoglu, Cihan
Abstract : Purpose: The purpose of this study is to further explore the effects of customer participation (CP) and service personal values (SPVs) on cruise customer satisfaction (CS) and customer loyalty (CL) by applying the empirical research approach. Design/methodology/approach: A self-administered questionnaire was prepared and used to collect data. Exploratory factor analysis and structural equation modeling analysis was used to test the proposed model and hypotheses. Findings: The empirical results indicate that CP positively influences SPVs, CS and CL. SPVs have a significant and positive impact on CS as well. Moreover, the study also finds that collectivism has a strong positive effect on CP. Price sensitivity negatively moderates the relationship among CP, CPV, CS and CL. Research limitations/implications: The generalizability of the current study findings should be considered or scrutinized in light of the fact that limited samples and cross-sectional data were used. This limitation positions the findings as a continuation of the developing path toward a better understanding of customer behavior rather than a definitive conclusion. Practical implications: The study results show that CP has a positive direct effect on SPVs, CS and CL. Even though many researchers have verified the importance and function of CP, there is a lack of literature, which assesses the influence of CP in a cruise industry context. By focusing on this gap, this research makes it feasible to empirically analyze the different effects of CP in relation to SPVs, CS and CL in Chinese cruise preferences. Social implications: The study results suggest that CP is a new predictor of CS and CL in the cruise industry. Thus, creating a positive experience through participation is crucial. As customers are co-producers, it is beneficial for the cruise companies to raise labor productivity and reduce cost by guiding and stimulating them to take part in the service-producing process. Originality/value: Based on the perspective of service-dominant logic, the purpose of this study is to shed light on the formation process of loyalty behavior of Chinese cruise tourists. The empirical results indicate that CP positively influences SPVs, CS and CL. SPVs have a significant and positive impact on CS as well. Moreover, the study also finds that collectivism has a strong positive effect on CP. Price sensitivity negatively moderates the relationship among CP, CPV, CS and CL. Abstract : 标题:中国邮轮游客的忠诚度:顾客参与和服务个人价值观的影响 Purpose: 本研究通过实证研究方法, 旨在深入探讨顾客参与(CP)与服务个人价值观(SPVs)对邮轮游客满意度(CS)与顾客忠诚度(CL)的影响。 Design/methodology/approach: 本文编制了一份自填问卷用于收集数据。采用探索性因子分析(EFA)和结构方程模型(SEM)分析进行模型和假设检验。 Findings: 结果表明, CP对SPVs、CS、CL均有正向影响。SPVs对CS也有显著的正向影响。此外, 本研究还发现, 集体主义对CP有很强的正向影响, 价格敏感性对CP、CPV、CS和CL之间的关系起负向调节作用。 Research limitations/implications: 鉴于样本有限和横断面数据的采用, 应仔细考虑和检查本文研究结果的普遍性。这一局限意味着本研究结果是顾客行为研究道路上的延续, 而不是一个确定的结论。 Practical implications: 研究结果表明, CP对SPVs、CS、CL有直接的正向影响。尽管许多研究者已经证实了CP的重要性和作用, 但是对于CP在邮轮业中的影响的评价文献还很缺乏。基于对这一研究空白的关注, 本文通过实证研究, 分析在中国人的邮轮偏好中, CP对SPVs、CS、CL的不同影响。 Social Implications: 研究结果表明, CP是邮轮行业CS和CL的一个新的预测因子。因此, 通过参与来创造积极体验是至关重要的。由于顾客是共同生产者, 通过引导和激励他们参与服务生产过程, 有利于提高邮轮公司的劳动生产率, 降低成本。 Originality/value: 基于服务主导逻辑的视角, 本研究旨在揭示中国邮轮游客忠诚行为的形成过程。实证结果表明, 顾客参与(CP)对顾客个人价值(SPVs)、顾客满意度(CS)和顾客忠诚度(CL)具有正向影响。SPVs对CS也有显著的正向影响。此外, 本研究还发现, 集体主义对CP有很强的正向影响, 价格敏感性负向调节CP、CPV、CS和CL之间的关系。 关键词: 关键词 顾客参与, 服务个人价值, 顾客忠诚度, 价格敏感度, 中国邮轮游客 论文类型: 研究论文 Abstract : La lealtad de los clientes chinos de cruceros: el impacto de la participación de los clientes y los valores personales del servicio Objetivo: El propósito de este estudio es explorar, en profundidad, los efectos de la participación del cliente (CP) y los valores personales del servicio (SPV) en la satisfacción del cliente de cruceros (CS) y la lealtad del cliente (CL) aplicando el enfoque de la investigación empírica. Diseño/metodología/enfoque: La obtención de datos se realizó a través de un cuestionario autoadministrado. El modelo y las hipótesis propuestas fueron contrastados a través del análisis factorial exploratorio (EFA) y el análisis de ecuaciones estructurales (SEM). Resultados: Los resultados empíricos indican que la CP influye positivamente en los SPV, CS y CL. Los SPVs también tienen un impacto significativo y positivo en la CS. Además, el estudio también encuentra que el colectivismo tiene un fuerte efecto positivo en el CP. La sensibilidad al precio modera negativamente la relación entre CP, CPV, CS y CL. Limitaciones/implicaciones de la investigación: La posibilidad de generalizar las conclusiones del presente estudio debe considerarse teniendo en cuenta que se utilizaron muestras limitadas y datos transversales. Esta limitación hace que los hallazgos avancen en la senda para una mejor comprensión del comportamiento del cliente y no sean una conclusión definitiva. Implicaciones prácticas: Los resultados del estudio muestran que el CP tiene un efecto directo positivo en las SPVs, CS y CL. Aunque muchos investigadores han verificado la importancia y la función de la CP, falta literatura que evalúe la influencia de la CP en el contexto del sector de los cruceros. Al centrarse en esta carencia, esta investigación permite analizar empíricamente los diferentes efectos de la CP en relación con las SPVs, CS y CL en las preferencias de los cruceristas chinos. Implicaciones sociales: Los resultados del estudio sugieren que la CP es un nuevo predictor de la CS y la CL en el sector de los cruceros. Por tanto, crear una experiencia positiva a través de la participación es crucial. Dado que los clientes son coproductores, es beneficioso para las compañías de cruceros aumentar la productividad laboral y reducir los costes guiándolos y estimulándolos a participar en el proceso de producción del servicio. Originalidad/interés: Basado en la perspectiva de la lógica dominante del servicio, el propósito de este estudio es arrojar luz sobre el proceso de formación de la lealtad de los turistas chinos de cruceros. Los resultados empíricos indican que la participación del cliente (CP) influye positivamente en los valores personales del servicio (SPV), la satisfacción del cliente (CS) y la lealtad del cliente (CL). Los SPVs también tienen un impacto significativo y positivo en la CS. Además, el estudio también encuentra que el colectivismo tiene un fuerte efecto positivo en el CP. La sensibilidad al precio modera negativamente la relación entre CP, CPV, CS y CL. Palabras clave: participación del cliente, valores personales del servicio, lealtad del cliente, sensibilidad al precio, turistas chinos de cruceros. Tipo de investigación: Trabajo de investigación